The Non-Retroactivity of Constitutional Court Rulings - Bustamante Belaúnde, Alberto (1982)
This article analyzes the retroactivity system of the sentences of the Tribunal of Constitutional Guarantees, according to the Organic Law that regulates it and its alignment with the Peruvian Constitution. Within this framework, it explores the ideological and legal dynamics underlying the retroactivity system, focusing on its legal and constitutional treatment, with emphasis on two constitutional norms: article 187, referring to the retroactivity of laws, and article 300, referring to the non-retroactivity of sentences of the Tribunal that declare a norm unconstitutional. In this regard, the author questions the relevance of including retroactivity rules in the Constitution, in contrast to other legal systems that grant it a legal level or omit it. He also criticizes the arbitrary protection of exceptions in criminal, labor, or tax matters, and discusses the effectiveness of the retroactivity concept within the public law doctrine. Finally, it presents a concern for the retroactivity reflected in the Court’s Organic Law, which contains misinterpretations of Article 300 and permits the review of concluded judicial processes in cases of subsequent unconstitutionality, thereby undermining the principle of res judicata. In summary, the author concludes that the Constitution and the law reflect a mistrust in the judicial system and suggests that the legislation could have been better crafted to avoid contradictions and allow for greater flexibility and protection of constitutional rights.